MON-445 A Rare and Unusual Presentation of Adenoid Cystic Carcinoma as Thyroid Mass with Metastasis to the Lung - Maita, Yousef (J Endocr Soc, 2020)
Introduction: Adenoid cystic carcinoma is a rare form of cancer that most commonly originates within the secretory cells of the major and minor salivary glands. In rare and unusual cases, adenoid cystic carcinoma can present as Thyroid mass. Adenoid cystic carcinoma is described presenting in papillary carcinoma of thyroid and as poorly differentiated thyroid carcinoma with mixed or unclear histology. We describe the case of a patient diagnosed with poorly differentiated thyroid carcinoma with complete thyroidectomy later presenting with metastatic lung disease diagnosed as adenoid cystic carcinoma. Case Presentation: A 53-year-old male with history of palpable neck mass, lymphadenopathy, and hoarseness with a diagnosis of poorly differentiated thyroid carcinoma with unclear histology. He underwent total thyroidectomy with level 6 compartment neck dissection, laryngeal nerve sparing with tracheostomy tube. Patient presented 2 months’ post thyroidectomy with right facial swelling. Labs were significant for microcytic anemia with Hgb 10, MCV 71, TSH and metabolic panel within normal limits. Radiographic imaging demonstrated residual-recurrent malignancy in the thyroid bed, lymphatic disease, and compression of surrounding structures including trachea, distal right internal jugular, and right subclavian vein. Follow up radiographic studies showed a 1.7 x 4.6 x 5.5cm soft tissue mass behind the trachea at the level of previously resected mass. Multiple pulmonary nodules were noted. Image guided needle biopsy of largest left lung nodules carcinoma with adenoid cystic pattern. Final path report was metastatic adenoid cystic carcinoma. Conclusion: This case is unique in that it describes a rare and uncommon presentation of adenoid cystic carcinoma as metastatic thyroid carcinoma in a patient with prior history of thyroidectomy. Adenoid cystic carcinoma is a rare glandular malignancy that commonly presents as the second most common histologic subtype of salivary cancer. Adenoid cystic carcinoma as a histologic subtype has a high morbidity and mortality, if not identified and managed promptly. Prognosis and survival outcomes are poor with some studies comparing its prognosis to that of anaplastic carcinoma. This case also illustrates the complexity and diverse presentation of adenoid cystic carcinoma. The initial diagnosis in this patient was nonspecific with biopsy revealing poorly differentiated carcinoma. Adenoid cystic carcinoma was diagnosed later at time of disease progression to the lung. This case reviews the diagnostic workup, evaluation, and appropriate management of adenoid cystic primary thyroid carcinoma. In addition, it evaluates the appropriate differential diagnosis in patients enlarging neck mass and progressive thyroid cancer.